Challenging the Ostwald rule of stages in mechanochemical cocrystallisation. Issue 37 (12th August 2020) - Germann, Luzia S.; Arhangelskis, Mihails; Etter, Martin; Dinnebier, Robert E.; Friščić, Tomislav
Abstract : The choice of milling assembly (jar and ball material, number and size of balls) can be used to direct polymorphism in mechanochemical cocrystallisation, enabling the selective synthesis, and even reversible interconversion of cocrystal polymorphs. Abstract : Mechanochemistry provides an efficient, but still poorly understood route to synthesize and screen for polymorphs of organic solids. We present a hitherto unexplored effect of the milling assembly on the polymorphic outcome of mechanochemical cocrystallisation, tentatively related to the efficiency of mechanical energy transfer to the milled sample. Previous work on mechanochemical cocrystallisation has established that introducing liquid or polymer additives to milling systems can be used to direct polymorphic behavior, leading to extensive studies how the amount and nature of grinding additive affect reaction outcome and polymorphism. Here, focusing on a model pharmaceutical cocrystal of nicotinamide and adipic acid, we demonstrate that changes to the choice of milling media ( i.e. number and material of milling balls) and/or the choice of milling assembly ( i.e. jar material) can be used to direct polymorphism of mechanochemical cocrystallisation, enabling the selective synthesis, and even reversible and repeatable interconversion of cocrystal polymorphs. While real-time mechanistic studies of mechanochemical transformations of metal–organic materials have previously suggested that reactions follow a path described by Ostwald's rule of stages, i.e . from metastable to increasingly more stable product structures, the herein presented systematic study presents an exception to that rule, revealing that modification of energy input in the mechanochemical system, combined with a small energy difference between polymorphs, permits the selective synthesis of either the more stable room temperature form, or the new metastable high-temperature form, of the target cocrystal.